Cross-Cultural Communication Nano Tips with Jessica Chen. - Chen, Jessica (linkedin.com, 2022)
Learn how to develop cultural awareness, cross-cultural working styles, and self-confidence in a global world. Plus, explore how to lead an international team effectively.